The profile of construction delay cases - Loo, Jenny Shih Yein (2012)
Construction industry has been increasingly recognizing the need for more efficient and timely projects completion. However, there remain a number of unexpected problems and changes from the original design. This will arise during the construction phase which often leads to many negative effects such as increased costs, lost productivity and revenue, contract termination, arbitration or litigation and even total abandonment of the project. Therefore, this research is set out to develop a profile of the delay in construction projects which lead to disputes. The profiling of the cases has been done based on the year, types of parties involved, time of delay disputes occur, nature of delay disputes and court judgment for the construction delay disputes that have been occurring in Malaysian construction industry. The approach adopted in this research is case law based; only cases in Malaysia between years 1961-2010 reported by Malayan Law Journal specifically centered on issue of delay disputes will be centered in this study. A total number of 18 cases were studied and the results show that the number of construction delay disputes cases is the highest between years 1991-2000. Most of the causes of delay dispute incurred in construction industry being debated in the court suit are mainly committed by the employer which includes late site possession, late payment, late instructions, late drawings and specifications as well as suspensions of work. It also highlighted that most delay disputes cases in construction industry generally occurred when financial conflict such as loss of profit, damages claim, non-payment reimbursement, noncertified work done and so forth between the contractual parties take place as a result of construction delay. In summary, findings of this research will be able to increase the awareness of the construction players of the current scenario in relation to construction delay issues as well as to assist them in addressing and overcoming the problems associated to delay disputes in Malaysian construction industry.